Pengaruh Tunjangan Karyawan terhadap Kinerja Karyawan di Bank Pembiayaan Rakyat Syariah (BPRS) Bakti Artha Sejahtera (BAS) Sampang - Robiatul Amina; Wadhan Wadhan (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2016)
The banks activities in general is a business that is based on the trust of society, therefore the managers professionalism  who are in it constituteing a necessity that can not be negotiable. Factors that the most influentsial in the bank's success in achieving its objectives is the workforce or employees, employees take an active role in setting plans, systems, processes and objectives to be achieved. Strategies to improve employee’s performance are by way of giving allowance to employees. Allowances are given additional compensation based on the company policy towards all employees in an effort to improve their welfare. The purpose of this research is the first: researcher wants to know the effect of employee’s allowance to employee’s performance in the BankPembiayaan Rakyat Syariah (BPRS) of Bakti Artha Sejahtera (BAS) Sampang; second, the researcher wants to know the employeess allowance are most influential on the employee’s performance in the Bank Pembiayaan Rakyat Syariah (BPRS)of Bakti Artha Sejahtera (BAS) Sampang. In this research, using a quantitative approach with the technique of multiple linear regression analysis. The data used are primary data obtained through questionnaires. The sample used 45 respondents, all employees in BPRS Artha Bakti Sejahtera (BAS) Sampang and all employees in each cash office of Banyuates, cash office of Omben, cash office of Sreseh and cash office of Camplong. From the research result of the hypothesis testing F-test can be summed up all the independent variables are significantly influence towards employee performance in BPRS Artha Bakti Sejahtera Sampang by comparing the value Fcount> Ftable with each large (16.655> 3.22) with significantly smaller level 0, 00 of the standard significant 0.05. The research results T-test indicate that variable of compulsory allowance have the greatest influence on employee performance. It was stated by the results of Test-T produces a correlation coefficient tcount = 4.032> ttable = 2.017 with a significance level of 0.000 <0.05 (5%). While the variable allowances not required to have the lowest influence on employee performance. It was stated by t-test produces a correlation coefficient value tcount = 2,079> t table = 2.017 with a significance level of 0.044 <0.05 (5%). From the result of the  determination coefficient (R2) using SPSS, by looking at the acquisition of adjusted R square of 0.416. That is 41.6% variable of employee’s performance affected by compulsory allowance and no compulsory allowance, while the remaining 58.4% can be explained by other factors that are not described in this research.